Miracles of Our Lady - Berceo, Gonzalo de, active 13th century (Book collections on Project MUSE., 2015)
Miracle tales, in which people are rewarded for piety or punished for sin through the intervention of the Virgin Mary, were a popular literary form all through the Middle Ages. Milagros de Nuestra Sehora, a collection of such stories by the Spanish secular priest Gonzalo de Berceo, is a premier example of this genre; it is also regarded as one of the four most important texts of medieval Spain. Difficulties in translating this work have made it unavailable in English except in fragments; now Spanish-language scholars Richard Terry Mount and Annette Grant Cash have made the entire work accessi.